Research seedbeds in virtual modality. Pedagogical strategy: From management to communication and scientific dissemination - Martínez-Daza, Magda Alejandra (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim was to systematize the pedagogical strategy of training and evaluation of research, oriented to undergraduate students linked to a virtual seedbed, which leads to academic-scientific communication and dissemination. A qualitative methodology was used based on the model for the systematization of experiences that describes five moments (planning; design; implementation; tutoring and evaluative follow-up). It showed that research training requires knowledge management aspects related to: people, pedagogy, didactics, technological resources, processes, techniques and instruments of alternative evaluation and cognitive tools, integrated to a virtual learning environment (EVA). These constitute quality indicators.